The Optimum Vibration of the Compressive Strength of Concrete Specimen - Karisma, Dwifi Aprillia; Candra, Agata Iwan; Ali, Mahardi Kamalika Khusna; Sari, Tiara Sherlyta; Pertiwi, Sheila Ananda Putri (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2022)
Concrete is the primary material in construction, so it needs further research to get good quality concrete. The quality and durability of concrete are influenced by the amount and shape of the air cavity inside the concrete. With vibrating, the air that is inside the concrete will be lost. The benefits of vibration will only be achieved if planned and implemented with a suitable method. With proper vibration, the air in the concrete will come out and make porous concrete. Reduction or removal of air cavities will make concrete mixes strong with low permeability, increasing the durability of concrete. This study aims to determine the optimum strong vibrating on the compressive strength of Fc' 21,7 Mpa concrete. Vibrating will be performed on cylinder concrete samples with a duration time of 3 minutes and with different variations in acceleration 160 m/s2, 170 m/s2, 180 m/s2, 190 m/s2, 200 m/s2, variation velocity 140 mm/s, 150 mm/s, 160 mm/s, 170 mm/s, 180 mm/s, displacement variation 600 mm, 800 mm, 1000 mm, 1200 mm, 1500 mm. Each variation consists of 7 concrete samples. These tests were performed with methods of external vibrating by using MBT Vibrating table CO-410 in fresh concrete. Compressive strength testing is carried out at 28 days. This study shows that the optimum strong vibrating with acceleration 180 m/s2, velocity 160 mm/s, and displacement 1000 mm with the resulting compressive strength is Fc' 23.06 MPa. So that knowing the optimum vibration strength can be the basis for the implementation of vibration to get the planned concrete quality.